Representasi Nilai Lokalitas Pada Tayangan TV CNN Indonesia Program Inside Jawa Barat - Raguan , Sopia; Supiarza, Hery; Nafsika, Salsa Solli (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This study discusses the representation of locality values in CNN Indonesia's Inside Jawa Barat program. The presence of Sistem Siaran Jaringan (SSJ) implementation rules in Undang-Undang No. 32 of 2002 opens up opportunities for the establishment of local television stations in Indonesia to create programs that raise local issues. Inside Jawa Barat is a show that tries to present local genius in an interesting manner, becoming a significant entity in providing dynamics for the existence of local television in Indonesia. This study aims to determine the representation of locality values in the Inside Jawa Barat program and how the program implements government regulations by creating shows that focus on local issues. Analytical descriptive qualitative research methods, including observation, documentation, literature studies, and semiotic concepts, were used in collecting all research data, with episode 30 of the Inside Jawa Barat program selected as the research subject. The results showed that Inside Jawa Barat succeeded in portraying the values of locality through the presentation of programs that highlight the culture, traditions, and lives of the people of West Java. Analysis using John Fiske's semiotic theory reveals that signs in the Inside Jawa Barat program create an understanding of reality, representation, and ideology as the embodiment of locality values represented by television programs. The conclusion of this study shows that the Inside Jawa Barat program not only complies with government regulations but also presents content about local values. The implications of this research can serve as a reference for the television industry to develop programs that comply with government regulations and highlight the wealth of local values.